2022
DOI: 10.5603/gp.a2022.0109
|View full text |Cite
|
Sign up to set email alerts
|

Epidural anesthesia during childbirth — retrospective analysis of maternal and neonatal results

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Ginekologia Polska" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…It is still controversial whether intrathecal analgesia on labor increases the rate of instrumental and cesarean delivery. Previous studies have shown that epidural labor analgesia increased the risk of instrument delivery, but contrary to conventional wisdom, the incidence of cesarean section reduced [31–33]. A meta-analysis showed that epidural anesthesia prolongs the duration of the first and second stages of labor [34].…”
Section: Discussionmentioning
confidence: 99%
“…It is still controversial whether intrathecal analgesia on labor increases the rate of instrumental and cesarean delivery. Previous studies have shown that epidural labor analgesia increased the risk of instrument delivery, but contrary to conventional wisdom, the incidence of cesarean section reduced [31–33]. A meta-analysis showed that epidural anesthesia prolongs the duration of the first and second stages of labor [34].…”
Section: Discussionmentioning
confidence: 99%
“…Epidurals are very powerful at relieving labor pain, but they are also associated with longer first and second stages of labor, and a higher risk of oxytocin augmentation, episiotomies, and operative deliveries [ 48 , 53 , 55 , 56 ]. Although the mechanisms are not fully understood, longer labor may result from a decrease in uterine activity and slower dilation of the cervix [ 57 ], possibly due to a drop in endogenous oxytocin [ 58 ].…”
Section: Discussionmentioning
confidence: 99%